Answer:
m=-3/7
Step-by-step explanation:
m=rise/run=Δy/Δx
m=y2−y1/x2−x1
m=10−7/−4−3
m=3/−7
m=−3/7
Answer:
<h2>-5</h2><h2>-6, -7, -8, -9, etc.</h2>
Step-by-step explanation:
<h2>Hopes this helps. Mark as brainlest plz!</h2>
Answer: C
Step-by-step explanation:
Answer:
-142
Step-by-step explanation:
You seem to have an arithmetic sequence with first term -66 and common difference (-68-(-66)) = -2. The general term of such a sequence is given by ...
an = a1 +d(n -1) . . . . . for first term a1 and common difference d
We want to evaluate this equation for a1 = -66, d = -2, n = 39:
a39 = -66 -2(39 -1) = -66 -76 = -142
The 39th term is -142.